Comparative feedlot performance of individually fed purebred Hereford steers of comprest and conventional type - Ingalls, James E., author; Stonaker, Howard H., advisor; Washburn, L. E., committee member; Clark, Andrew Giles, committee member; Whitney, Robert S. (Robert Shannon), 1912-, committee member; Wheeler, S. S. (Sherman Shaw), 1901-, committee member (Colorado State University. Libraries, 1948)
To view the abstract, please see the full text of the document.
Keywords: Feeds; Hereford cattle